Developing Adult Vaccination Ecosystem in India: Current Perspective and the Way Forward - Canna Jagdish Ghia; Gautam Sudhakar Rambhad (SAGE Publishing, 2021)
Introduction: A high burden of vaccine-preventable diseases, increasing elderly population, immunosenescence, and emerging drug resistance emphasize the need for robust adult immunization in India. While immunization guidelines from various societies exist, there is inadequate implementation of the same. Aim: We undertook this narrative review of the adult vaccination ecosystem in India to (i) gain insights into existing adult vaccination practices, (ii) identify barriers to adult vaccination and possible solutions, and (iii) improve collaboration between various stakeholders to help establish adult vaccination centers in the country. Results: Besides the high cost and lack of insurance coverage, the lack of adult vaccination centers contributes to the low coverage of adult immunization. Discussion: These challenges can be addressed through multiple approaches including community awareness and immunization programs, setting up mobile vaccination vans, patient/consumer education, and adequate training of healthcare providers. Successful implementation of these strategies requires active collaboration between the government, hospitals, different stakeholders, and policymakers.